Test of Acceptance and Fe Levels of Green Beans with the Addition of Katuk Leaves “PUCAHITUK” as a Teenager Snack to Prevent Less Blood - Anggiani Tetra Putri Harahap; Mujayanto; Nuning Marina Pengge; Ani Intiyati (Journal of Nutrition Explorations, 2023)
According to (WHO, 1992) anemia is a condition where the Hb level is lower than the normal limit. The purpose is to determine the acceptability and levels of iron in processed mung bean pudding products with the addition of katuk leaves as a source of iron snacks for adolescents. This research method is experimental. Data collection is obtained from organoleptic tests and Fe levels in the laboratory. Statistical analysis used the Kruskall Wallis and Mann Whithney test. The results showed organoleptic properties, the most preferred formulation by the panelists was the PKU formulation with a ratio (80:30). The highest Fe content in the control code was PKA at 18.91 mg/kg. Nutritional Adequacy Ratio recommends intake of 16 mg of Fe per day as a dietary effort to prevent anemia. If the snack is given 2 times with a portion of 10% of daily needs = 10% x 16 mg = 1.6 mg. Meanwhile, the Fe content of PUKAHITUK Pudding was <0.028 mg/kg. If the green bean pudding and katuk leaves weigh 90 g/cup, they contain 90gr/1000 x < 0.028 mg = 0.0252 mg/cup. It can be concluded that 1 cup of pudding does not meet the snack needs for teenagers.